The Library and Computerization on Information Services - Bethel Chidiebere Uzoagba; Catherine Obi Elemi; Godwin, Oberhiri Orumah (International Journal of Global Sustainable Research, 2024)
This study was undertaken to assess the prospects of computerization in public library Onitsha in Anambra state. The purpose of the study is to know the future possibilities and benefits of computerization in the storage of information, retrieval, and to find the effects of computerization on information services. In order to educate the public on the importance of computerization and internet data base library. It includes the problems and how it could be solved, to enhance and create our atmosphere conducive and comfortable for learning. The descriptive survey design was adopted, while the simple random sampling techniques was used to select a sample size of (50) fifty persons and (45) forty five were retrieved as respondents. Data was collected were compiled and analyzed in frequency table and percentage method. The findings obtained; consequently revealed that computerization is a welcome idea which enables the clientele of the library and staff to be motivated. It has been discovered that computerization of the library service will enhance information storage, packaging and retrieval in the establishment. On the above findings, conclusion were drawn and recommendation made for further studies